Morphophysiology and ultrastructure of the male reproductive accessory glands of the bats Carollia perspicillata, Glossophaga soricina and Phyllostomus discolor (Chiroptera: Phyllostomidae) - Martins, Fabiane F. [UNESP] (2016)
The male reproductive accessory glands (RAGs) are important organs that contribute to the secretion of different substances that composed the ejaculate. Despite this important function, their composition, anatomy and function vary widely between species. Thus, the RAGs of three species of phyllostomid bats were morphologically and ultrastructurally characterized and compared in this study. The RAGs of the three analyzed species are composed of a prostate and a pair of bulbourethral glands (BG). In all species, the prostate is composed of three well-defined regions (ventral, dorsolateral and dorsal regions). The ventral region showed an atypical epithelium (undefined) with no obvious cellular limits and a holocrine PAS-positive secretion. The dorsolateral region of Carollia perspicillata and Phyllostomus discolor showed a pseudostratified cubic morphology, and that from Glossophaga soricina had a columnar morphology endowed with cytoplasmic projections and stereocilia. The dorsal region of the three analyzed species is composed of a pseudostratified columnar epithelium endowed with stereocilia; however, G. soricina also presented cytoplasmic projections in the apical portions of the secretory cells similar to those in the dorsolateral region. The BG of the three analyzed species are composed of a pseudostratified columnar epithelium including basal and PAS-positive secretory cells. In conclusion, this study morphologically and ultrastructurally characterized the RAGs of three species of phyllostomid bats, demonstrating the presence of a novel third prostatic region in species of this family. The results also showed the absence of seminal vesicles and ampullary glands, and better characterized the holocrine pattern of the prostatic ventral region, which is unique to bats.